How big is the elephant in the room? Estimated and actual IT costs in an online behaviour change trial - Murray Elizabeth; Linke Stuart; Khadjesari Zarnie; Godfrey Christine; O'Donnell Orla; McCambridge Jim; Wallace Paul (BMC Research Notes, 2010)
Abstract Background The practical and methodological challenges inherent in online behaviour change studies are both novel and complex. We relate our experiences of estimating and managing information technology (IT) research and intervention costs in an ongoing internet trial in the hope that others will find this information useful. Findings Actual IT costs were approximately twice those that had been originally estimated by external contractors. These original estimates for IT costs allowed little scope for the identification of new needs, which was intrinsic to the iterative nature of the research enterprise. Conclusions Making greater provision for the uncertain nature of these costs in future studies is a key practical lesson for the planning of future online behaviour change studies.